Computer Training and Assistance for Microsoft Office Word Programs for Teachers Raudhatul Athfal (RA) Al-Lathif Padalarang Kab. West Bandung: Pelatihan Dan Pendampingan Komputer Program Microsoft Office Word Kepada Guru Raudhatul Athfal (RA) Al-Lathif Padalarang Kab. Bandung Barat - Agry Alfiah (Mattawang: Jurnal Pengabdian Masyarakat, 2022)
Raudhatul Athfal (RA) Al-Lathif is an early childhood education level school under the ministry of religion located on Jl. Landscape of Padalarang Regency No. 31, Jayamekar, Padalarang, West Bandung Regency, West Java. The problem faced is the lack of competence of the Raudhatul Athfal (RA) Al-Lathif teachers, especially when using the Microsoft Office Word computer program. The aim is to provide training and mentoring of Microsoft Office Word computer programs to teachers Raudhatul Athfal (RA) Al-Lathif in order to improve teacher competence, especially the use of technology in the learning process. The method of implementing this activity has several stages, namely data collection, problem identification, needs analysis, design and preparation, training implementation and activity documentation. During the training, the teachers were given a printed training module and then they did the exercises by practicing using the Microsoft Office Word computer program. The result of this activity is the establishment of cooperation in order to accelerate efforts to increase skills in operating Microsoft Office Word to process data, make learning implementation plans, create teaching materials and documents in the form of reports and correspondence, resulting in work efficiency to complete various activities to process data using Microsoft Office. Word quickly and precisely. Abstrak Raudhatul Athfal (RA) Al-Lathif merupakan sekolah jenjang pendidikan anak usia dini dibawah kementerian agama yang berlokasi di Jl. Bentang Padalarang Regency No.31, Jayamekar, Padalarang, Kabupaten Bandung Barat, Jawa Barat. Adapun masalah yang dihadapi yaitu kurangya kompetensi yang dimiliki para guru Raudhatul Athfal (RA) Al-Lathif terutama pada saat penggunaan program komputer Microsoft Office Word. Tujuannya adalah untuk memberikan pelatihan dan pendampingan program komputer Microsoft Office Word kepada guru Raudhatul Athfal (RA) Al-Lathif agar dapat meningkatkan kompetensi guru terutama pemanfaatan teknologi pada proses pembelajaran berlangsung. Metode pelaksanaan kegiatan ini ada beberapa tahapan yaitu pengumpulan data, identifikasi masalah, analisis kebutuhan, perancangan dan penyusunan, pelaksanaan pelatihan dan dokumentasi kegiatan. Pada saat pelatihan, para guru diberikan modul pelatihan yang telah dicetak kemudian mereka mengerjakan latihan dengan mempraktekkannya menggunakan program komputer Microsoft Office Word. Hasil dari kegiatan ini terjalinnya kerjasama agar dapat mempercepat upaya peningkatan keterampilan dalam mengoperasikan Microsoft Office Word untuk mengolah data, membuat rencana pelaksanaan pembelajaran, membuat bahan ajar maupun dokumen berupa laporan dan surat menyurat, sehingga menghasilkan efisiensi kerja untuk menyelesaikan berbagai aktifitas mengolah data menggunakan Microsoft Office Word secara cepat dan tepat.